(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Nowadays, automotive industry is continuing to strive for light weight vehicle in improving fuel efficiency and emissions reduction. To produce a better performance it is important to design vehicles with optimum weight. The automotive industry is optimizing designs to reduce vehicle body weight by means of topology optimization and by use of alternative materials. However, the modified design must meet several performance criteria, mainly stiffness and strength. This paper aims to employ theoretical, numerical, experimental analysis and topology optimization technique to propose an optimal design of brake pedal used in three wheeler segment. The material used for an existing brake pedal is unchanged as this study focuses on reducing weight of existing brake pedal without material substitution. The digital model of an existing brake pedal was generated with the aids of reverse engineering technique and computer aided design (CAD) software. Finite element analysis and topology optimization will be performed by using Altair Opti-Struct software under linear static stress analysis and modal analysis. Finally, a new light weight brake pedal design will be proposed with existing brake pedal without sacrificing its performance requirement.